CRITIQUE ON THE CONCEPT OF PSYCHONEUROIMMUNOLOGY (PNI) IN AYURVEDA AND YOGA w.s.r. TO COVID-19 PANDEMIC (International Journal of Ayurveda and Pharma Research, 2021)
The COVID-19 outbreak has prompted significant levels of psychological distress and critical effect on emotional wellness as well as challenged health care systems across the globe. Such distress is accompanied with alterations in immune function including expanded danger of viral respiratory tract infections. It has shaken the entire world with this worldwide crisis. The panic situation created by the disease along with the unfamiliar way of conduct imposed several psychological impacts on human life. Many can’t cope up with the situation on their own and are in need of an intervention such as Psychological First Aid. Fear, anxiety, future concerns, interpersonal relationships issues, behavioral issues, domestic abuses, separation anxiety are a few among the psychological issues reported. It is basic to comprehend that these depend on a more profound comprehension of how choice less mindfulness coordinates the neurological, immune and metabolic frameworks with psychological processes to work overall. In this review article, an attempt has been made to critically enlighten the ancient and recent development of the Psychoneuroimmuology (PNI) in Ayurveda and Yoga in concern with Covid-19 Pandemic.